2003
DOI: 10.1002/yea.991
|View full text |Cite
|
Sign up to set email alerts
|

Response to acetaldehyde stress in the yeast Saccharomyces cerevisiae involves a strain‐dependent regulation of several ALD genes and is mediatedby the general stress response pathway

Abstract: One of the stress conditions that yeast may encounter is the presence of acetaldehyde. In a previous study we identified that, in response to this stress, several HSP genes are induced that are also involved in the response to other forms of stress. Aldehyde dehydrogenases (ALDH) play an important role in yeast acetaldehyde metabolism (e.g. when cells are growing in ethanol). In this work we analyse the expression of the genes encoding these enzymes (ALD) and also the corresponding enzymatic activities under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 36 publications
1
67
0
Order By: Relevance
“…An early study showed that exogenously added acetaldehyde at a concentration of 1,000 mg/liter reduced the fermentation rate of glucose by S. cerevisiae by 30% (17). From a more fundamental point of view, such an addition of acetaldehyde initiates a transcriptional response in yeast cells that changes the expression of HSP genes (1), the genes encoding aldehyde dehydrogenases (ALD genes [2]) in order to allow the cells to use ethanol and acetaldehyde as carbon and energy sources under several circumstances.…”
Section: Fig 4 Cellular Fluorescence During Fermentationmentioning
confidence: 99%
“…An early study showed that exogenously added acetaldehyde at a concentration of 1,000 mg/liter reduced the fermentation rate of glucose by S. cerevisiae by 30% (17). From a more fundamental point of view, such an addition of acetaldehyde initiates a transcriptional response in yeast cells that changes the expression of HSP genes (1), the genes encoding aldehyde dehydrogenases (ALD genes [2]) in order to allow the cells to use ethanol and acetaldehyde as carbon and energy sources under several circumstances.…”
Section: Fig 4 Cellular Fluorescence During Fermentationmentioning
confidence: 99%
“…A few years ago several proteins were detected at a higher concentration in acetaldehyde-treated cells than in ethanol-treated cells, and it was thought likely that one of those proteins was Hsp90p (30). Recent studies carried out in our laboratory have demonstrated that the addition of acetaldehyde to exponentially growing cells provokes an induction in the transcription of stress response genes, such as HSP genes (3), and of aldehyde dehydrogenase (ALD) genes (4). The induction of all of these genes by acetaldehyde is positively regulated by Msn2/4p and Hsf1p proteins, while their expression is repressed by protein kinase A (4).…”
mentioning
confidence: 99%
“…Acetaldehyde, ethanol and acetate metabolism in S. cerevisiae is complex [79] because several enzymes are involved with a dependence on the cell's redox balance. The two enzymes ultimately responsible for their metabolic pathways are alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH), each of which consists of several isoenzymes.…”
Section: Acetaldehydementioning
confidence: 99%
“…The presence of acetaldehyde is one of the many stress conditions that yeast cells may encounter [79,82]. Several heat-shock proteins (HSP) genes are induced that are also involved in the response to other forms of stress (for example, ethanol) [83].…”
Section: Acetaldehydementioning
confidence: 99%